2013
DOI: 10.1002/ajmg.a.35727
|View full text |Cite
|
Sign up to set email alerts
|

Pure de novo partial trisomy 6p in a girl with craniosynostosis

Abstract: Duplications of chromosome 6p are rarely reported. We present the case of a girl with a de novo trisomy 6p12.3-p21.1 who showed clinical features characteristic of this syndrome, notably facial anomalies, psychomotor delay, and recurrent respiratory tract infections. The most striking feature, however, was craniosynostosis, manifested by the premature fusion of the right coronal and sagittal sutures. A review of the literature revealed that the presence of abnormal fontanelles and sutures is relatively common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…RUNX2 [Varvagiannis et al, 2013] and BMP5 [Villa et al, 2007] have correctly been proposed to explain craniosynostosis and craniofacial abnormalities; on the other hand, there are cases that have dysmorphic features without the involvement of the RUNX2 and BMP5 genes in the triplicated chromosomal segments. Su et al [2012] suggested 9 other genes: FOXQ1, FOXF2, FOXC1, NRN1, EDN1, ATXN1, DEK , E2F3 , and NRSN1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RUNX2 [Varvagiannis et al, 2013] and BMP5 [Villa et al, 2007] have correctly been proposed to explain craniosynostosis and craniofacial abnormalities; on the other hand, there are cases that have dysmorphic features without the involvement of the RUNX2 and BMP5 genes in the triplicated chromosomal segments. Su et al [2012] suggested 9 other genes: FOXQ1, FOXF2, FOXC1, NRN1, EDN1, ATXN1, DEK , E2F3 , and NRSN1.…”
Section: Discussionmentioning
confidence: 99%
“…Particular findings are generally reported. Villa et al, 2007;Su et al, 2012;Varvagiannis et al, 2013] . Additionally, the translocation can involve different chromosomes, and disruption or deletion of different located genes could have a significant pathogenic effect that contributes to define specific phenotypes ( table 2 ).…”
Section: F 6p21pter/20p13mentioning
confidence: 99%
See 2 more Smart Citations
“…RUNX2 deficiency results in deficient skull ossification in the context of cleidocranial dysplasia. Importantly, RUNX2 duplication [Mefford et al, 2010], triplication [Varvagiannis et al, 2013] and quadruplication [Greives et al, 2013] have been reported in patients with syndromic CS and there appears to be a direct correlation between the gene copy number and the severity of the phenotype. Our group identified two rare missense variants, M175R and R237C in two of 137 patients with sNCS.…”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%